Cover Feature: High‐Performance and Low‐Cost Sodium‐Ion Anode Based on a Facile Black Phosphorus−Carbon Nanocomposite (ChemElectroChem 9/2017). Issue 9 (7th August 2017) - Peng, Bo; Xu, Yaolin; Liu, Kai; Wang, Xiaoqun; Mulder, Fokko M.
Abstract : The Inside Cover picture illustrates a black phosphorus–carbon nanocomposite that is synthesized from commercial red phosphorus and low‐cost super P carbon black. The material exhibits an excellent performance/cost ratio, remarkable capacity retention, and cycling stability as the anode for sodium‐ion batteries. More details can be found in the Communication by F. M. Mulder and co‐workers onpage 2140 in Issue 9, 2017 (DOI:10.1002/celc.201700345 ).